Hsa-miR223-3p circulating level is upregulated in Friedreich's ataxia and inversely associated with HCLS1 associated protein X-1, HAX-1. Issue 12 (7th January 2022) - Quatrana, Andrea; Morini, Elena; Tiano, Francesca; Vancheri, Chiara; Panarello, Luca; Romano, Silvia; Marcotulli, Christian; Casali, Carlo; Mariotti, Caterina; Mongelli, Alessia; Fichera, Mario; Rufini, Alessandra; et al.
Abstract: Frataxin (FXN) deficiency is responsible for Friedreich's ataxia (FRDA) in which, besides the characteristic features of spinocerebellar ataxia, two thirds of patients develop hypertrophic cardiomyopathy that often progresses to heart failure and premature death. Different mechanisms might underlie FRDA pathogenesis. Among them, the role of miRNAs deserves investigations. We carried out an miRNA PCR-array analysis of plasma samples of early-, intermediate- and late-onset FRDA groups, defining a set of 30 differentially expressed miRNAs. Hsa-miR223-3p is the only miRNA shared between the three patient groups and appears upregulated in all of them. The up-regulation of hsa-miR223-3p was further validated in all enrolled patients ( n = 37, Fc = +2.3; P < 0.0001). Using a receiver operating characteristic curve analysis, we quantified the predictive value of circulating hsa-miR223-3p for FRDA, obtaining an area under the ROC curve value of 0.835 ( P < 0.0001) for all patients. Interestingly, we found a significant positive correlation between hsa-miR223-3p expression and cardiac parameters in typical FRDA patients (onset < 25 years). Moreover, a significant negative correlation between hsa-miR223-3p expression and HAX-1 (HCLS1-associated protein X-1) at mRNA and protein level was observed in all FRDA patients. In silico analyses suggested HAX-1 as a target gene of hsa-miR223-3p. Accordingly, we report that HAX-1 is negatively regulated by hsa-miR223-3p in cardiomyocytes (AC16) and neurons (SH-SY5Y), which are critically affected cell types in FRDA. This study describes for the first time the association between hsa-miR223-3p and HAX-1 expression in FRDA, thus supporting a potential role of this microRNA as non-invasive epigenetic biomarker for FRDA.